Gift exchange and reciprocity in competitive experimental markets - Ernst Fehr; Georg Kirchsteiger; Arno Riedl (Institute for Advanced Studies (IHS), 1995)
One of the outstanding results of three decades of laboratory market research is that under rather weak conditions prices and quantities in competitive experimental markets converge to the competitive equilibrium. Yet, the design of these experiments ruled out gift exchange or reciprocity motives, that is, subjects could not reciprocate for a gift. This paper reports the results of experiments which do not rule out reciprocal interactions between buyers and sellers. Sellers have the opportunity to choose quality levels which are above the levels enforceable by buyers. In principle they can, therefore, reward buyers who offer them high prices. Yet, such reciprocating behaviour lowers sellers' monetary payoff and is, hence, not subgame perfect. The data reveal that a majority of sellers behave reciprocally and that this behaviour is anticipated by buyers. As a result, buyers are willing to pay prices which are substantially above sellers' reservation prices. These results indicate that reciprocity motives may indeed be capable of driving a competitive experimental market permanently away from the competitive outcome. The data, therefore, support the gift exchange approach to the explanation of involuntary unemployment.
Keywords: J41; J64; C91; C92; 330; gift exchange; reciprocity; experiments